2013
DOI: 10.1111/ijac.12113
|View full text |Cite
|
Sign up to set email alerts
|

Slurry‐Based Additive Manufacturing of Ceramics

Abstract: Most additive manufacturing (AM) techniques have in common that material is spread out as thin layers of a dried powder/granulate by a roller or a shaker system. These layers are mostly characterized by a low packing rate. On the other hand, appreciable densities can be reached by the use of ceramic slurries. In this context, the layer‐wise slurry deposition (LSD) has been developed. Specific features of the LSD process are reflected on the basis of already existing additive manufacturing technologies. The mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(32 citation statements)
references
References 19 publications
0
28
0
Order By: Relevance
“…A major concern at that time was, however, the deposition of uniform layers with a flat and smooth surface. Since then, technologies capable of repeatedly depositing thin layers of ceramic slurries to build up dense powder beds for S‐3DP and S‐SLS have been developed . A survey of recently published work reveals a great potential of this technology for the manufacture of dense powder compacts, comparable to those produced by classical powder processing, that is with low organic content.…”
Section: Am Technologies For Ceramicsmentioning
confidence: 99%
See 2 more Smart Citations
“…A major concern at that time was, however, the deposition of uniform layers with a flat and smooth surface. Since then, technologies capable of repeatedly depositing thin layers of ceramic slurries to build up dense powder beds for S‐3DP and S‐SLS have been developed . A survey of recently published work reveals a great potential of this technology for the manufacture of dense powder compacts, comparable to those produced by classical powder processing, that is with low organic content.…”
Section: Am Technologies For Ceramicsmentioning
confidence: 99%
“…In this context, one of the most successful technologies is stereolithography (SL), using ceramic slurries containing photosensitive resins for the layerwise buildup of ceramic compacts. So far, little work has been devoted to the development of AM processes for the deposition of thin layers using water‐based ceramic suspensions or pastes with low organic content …”
Section: Feasibility Of Am Processing Of Monolithic Ceramicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The VAT process was initially developed for polymeric materials; however, in recent years, there has been an increase in the manufacturing of ceramic parts using this technology. 19,[25][26][27] Chartier et al 28 have investigated the use of SLA for manufacturing ceramic structures and have demonstrated successful production of detailed and precise complex lattice systems. [21][22][23][24] Thus, the use of Stereolithography (SLA), based on photopolymer resins with suspended ceramic particles (by at least 40% volume) appears to be an alternative technology for producing complex 3D printed ceramic parts.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Thus, the use of Stereolithography (SLA), based on photopolymer resins with suspended ceramic particles (by at least 40% volume) appears to be an alternative technology for producing complex 3D printed ceramic parts. 19,[25][26][27] Chartier et al 28 have investigated the use of SLA for manufacturing ceramic structures and have demonstrated successful production of detailed and precise complex lattice systems. Wang and Dommati 29 have studied the printing process of zirconia using SLA, and have shown that high density ceramic parts based on complex geometries can be obtained.…”
Section: Introductionmentioning
confidence: 99%